Enhanced remediation of Cd-contaminated soil using electrokinetic assisted by permeable reactive barrier with lanthanum-based biochar composite filling materials - Li, Sen (Environmental technology, 2023)
Electrokinetic remediation (EK) combined with a permeable reactive barrier (PRB) is a relatively new technique for efficiently remediating Cd-contaminated soil in situ. Eupatorium adenophorum, which is a malignant invasive plant, was used to synthesise biochar and a novel lanthanum-based biochar composite (LaC). The biochar and LaC were used as cheap and environmentally benign PRB filling materials to remediate simulated and real Cd-contaminated soils. The pH and residual Cd concentration in the simulated contaminated soil during remediation gradually increased from the anode to the cathode used to apply an electric field to the EK-PRB system. However, the soil conductivity changed in the opposite way, and the current density first increased and then decreased. For simulated contaminated soils with initial Cd concentrations of 34.9 and 100.6 mg kg-1, the mean Cd removal rates achieved using LaC were 90.6% and 89.3%, respectively, which were significantly higher than those of biochar (P < 0.05). Similar results were achieved using natural soils from mining area and polluted farmland, and the Cd removal rates were 66.9% and 72.0%, respectively. Fourier-transform infrared and X-ray photoelectron spectroscopy indicated that there were many functional groups on the LaC surfaces. The removal mechanism of EK-PRB for Cd in contaminated soil includes electromigration, electroosmotic flow, surface adsorption, and ion exchange. The results indicated that the LaC could be used in the EK-PRB technique as a cheap and 'green' material to efficiently decontaminate soil polluted with heavy metals